2022
DOI: 10.1111/jth.15614
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant treatment for upper extremity deep vein thrombosis: A systematic review and meta‐analysis

Abstract: Background Data on anticoagulant treatment for upper extremity deep vein thrombosis (UEDVT) are largely derived from studies on usual site venous thromboembolism (VTE). Objectives The objective of this meta‐analysis was to evaluate the efficacy and safety of anticoagulant therapy for UEDVT. Patients/Methods A systematic search of MEDLINE and EMBASE was conducted for studies including patients with UEDVT. Primary outcomes were recurrent VTE and major bleeding. Secondary outcomes included clinically‐relevant non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
2
9
0
1
Order By: Relevance
“…Our results suggest that edoxaban-which is already approved for the treatment of proximal lower-limb DVT and EP in cancer patients-is effective and safe also for CRT of the upper extremities, with preservation of line function and resolution of thrombosis in almost the totality of patients and no evidence of MB and CRNMB. These findings are consistent with the results of a recent meta-analysis published by our group, which has shown that recurrent VTE, MB, and CRNMB are not significantly different in patients with upper extremity DVT who received different types of anticoagulant treatments, even if they are affected by cancer (21). The fact that our data have been obtained in a specific population of women with gynecologic cancer is important, because it provides novel information on a category of patients affected by cancers that are frequently associated with VTE and because CRT often occurs in women receiving chemotherapy for cancer (22).…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that edoxaban-which is already approved for the treatment of proximal lower-limb DVT and EP in cancer patients-is effective and safe also for CRT of the upper extremities, with preservation of line function and resolution of thrombosis in almost the totality of patients and no evidence of MB and CRNMB. These findings are consistent with the results of a recent meta-analysis published by our group, which has shown that recurrent VTE, MB, and CRNMB are not significantly different in patients with upper extremity DVT who received different types of anticoagulant treatments, even if they are affected by cancer (21). The fact that our data have been obtained in a specific population of women with gynecologic cancer is important, because it provides novel information on a category of patients affected by cancers that are frequently associated with VTE and because CRT often occurs in women receiving chemotherapy for cancer (22).…”
Section: Discussionsupporting
confidence: 92%
“…A recent systematic review on primary and secondary UEDVT found a low risk of recurrent thrombosis (including UEDVT, LLDVT and PE) of 3% (95% CI 2–4) over 13 months' follow‐up after a mean of 5 months anticoagulation 34 . However, most included patients had secondary UEDVT related to vascular access devices (60.8%) and cancer (56.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in UEDVT, the adverse events from additional interventions do not seem justified. Furthermore, the not insignificant rate of bleeding of 3%-4% annually with long-term anticoagulation 34 In the absence of such research, clinical equipoise remains between anticoagulation alone or more aggressive therapies as well as regarding the duration of anticoagulation to utilise in the management of idiopathic UEDVT.…”
Section: Summary and Implications For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent across the different subgroups of patients and the different anticoagulant agents. [51] In this case report, we detected ULDVT by US, including compression ultrasound (CUS), color-Doppler and combined techniques, which is the imaging modality test of choice. Indeed, its sensitivity and specificity ranges from 81–97% and 93–96%, respectively.…”
Section: Discussionmentioning
confidence: 99%